2017
DOI: 10.1037/ipp0000071
|View full text |Cite
|
Sign up to set email alerts
|

Low-Income Urban Filipino Mothers’ Experiences With Community Violence

Abstract: Community violence exposure has profound implications for individuals’ psychological well-being, and yet, little is known about its effects on parents residing in high-risk neighborhoods. Using qualitative interviews with 20 mothers living in informal settlement areas in the Philippines, this study examined (a) the parenting strategies that mothers use in response to community violence and (b) the protective factors that enhance their well-being. Content analyses revealed that the most frequently endorsed pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Moreover, poor Filipino individuals are highly committed to helping their families of origin; such a strong family orientation can enhance individuals’ sense of security and support during difficult times (Tuason, 2011). As found in a previous study, Filipino mothers reported relying on their spouse, children, and relatives to ease their anxiety about neighborhood dangers (Jocson & Garcia, 2017). Familism may thus serve a buffering role among low-income Filipino mothers who experience stressful events like community violence.…”
Section: Religiosity and Familism As Protective Factorssupporting
confidence: 54%
See 2 more Smart Citations
“…Moreover, poor Filipino individuals are highly committed to helping their families of origin; such a strong family orientation can enhance individuals’ sense of security and support during difficult times (Tuason, 2011). As found in a previous study, Filipino mothers reported relying on their spouse, children, and relatives to ease their anxiety about neighborhood dangers (Jocson & Garcia, 2017). Familism may thus serve a buffering role among low-income Filipino mothers who experience stressful events like community violence.…”
Section: Religiosity and Familism As Protective Factorssupporting
confidence: 54%
“…Thus, in the context of poor and dangerous neighborhoods, mothers may have the additional task of ensuring that children are safe, while also taking care of children’s physical, financial, and emotional needs. Indeed, low-income Filipino mothers report being fearful and anxious about their child’s safety and well-being because of violence in the community (Jocson & Garcia, 2017). Additionally, low-income Filipino mothers worry about their children’s involvement in other neighborhood risks and dangers such as drinking, gambling, and using or selling drugs (Ochoa, 2014).…”
Section: Community Violence Exposure and Maternal Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Philippines, there is indeed evidence suggesting that religiosity functions as a protective factor in adverse contexts. Qualitative studies showed that Filipino adults rely on prayers, religious faith, and support from a religious community when faced with difficult situations (Jocson & Garcia, 2017; Lagman et al, 2014; Tuason, 2011).…”
Section: Religiosity Spirituality and Psychological Well-beingmentioning
confidence: 99%
“…In the Philippines, religion is widely recognized as an important and powerful social institution, yet the direct contributions of religiosity and spirituality to Filipino parents’ psychological well-being and behaviors are largely unknown. Although there is some evidence on the benefits of religiosity and spirituality on coping behaviors (Jocson & Garcia, 2017; Lagman et al, 2014; Tuason, 2011), more studies are needed to identify which specific aspects of religiosity and spirituality may contribute to other aspects of well-being. In addition, the relation of religious and spiritual factors to both positive and negative parenting behaviors remains unexplored in the local context.…”
Section: Current Studymentioning
confidence: 99%